2016
DOI: 10.1088/0964-1726/25/7/077002
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the dynamic behaviors of an MRE isolator subjected to constant and alternating currents

Abstract: This paper presents the dynamic behaviors of a magneto-rheological elastomer (MRE) isolator by applying constant and time-varying exciting currents. As the first step, a shear type of the MRE isolator is devised with a simplified design. Then, the distributions of the magnetic field in the MRE isolator under both constant and alternating exciting currents are analyzed by commercial software (ANSYS). Subsequently, the dynamic performances of the isolator are experimentally evaluated by applying three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Over the past two decades, magnetorheological elastomer (MRE) has gained considerable attention in many engineering applications [1][2][3][4][5][6][7][8]. Being a solid analogy of magnetorheological fluid (MRF), MRE demonstrated its superiority over MRF for its fast response time, no sedimentation and sealing issues, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, magnetorheological elastomer (MRE) has gained considerable attention in many engineering applications [1][2][3][4][5][6][7][8]. Being a solid analogy of magnetorheological fluid (MRF), MRE demonstrated its superiority over MRF for its fast response time, no sedimentation and sealing issues, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Behrooz et al [5] reported a variable stiffness and damping isolator (VSDI) for vibration mitigation of structures. Shi et al [6] devised a vertical MRE isolator and investigated its dynamic behaviours when applied various current excitations. In civil engineering applications, Li et al [9] proposed a multilayer MRE base isolator for seismic protection of civil structures with more than 16 times increase in the stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…3. The clutch disk torsional damper (Chen, 2005), Geislinger coupling (Xiang and Geng, 2004), dual-mass flywheel torsional damper (Song et al, 2012;Shi et al, 2009), and positive-negative stiffness parallel torsional damper can be mounted on the power transmission path to reduce the fluctuation torque of the system (Liu et al, 2018).…”
Section: New Materials New Structures and New Technology Canmentioning
confidence: 99%